Preconception Exposure to Fine Particulate Matter Leads to Cardiac Dysfunction in Adult Male Offspring. Issue 24 (18th December 2018) - Tanwar, Vineeta; Adelstein, Jeremy M.; Grimmer, Jacob A.; Youtz, Dane J.; Katapadi, Aashish; Sugar, Benjamin P.; Falvo, Michael J.; Baer, Lisa A.; Stanford, Kristin I.; Wold, Loren E.
Abstract : Background: Particulate matter (particles < 2.5 μm [PM2.5 ]) exposure during the in utero and postnatal developmental periods causes cardiac dysfunction during adulthood. Here, we investigated the potential priming effects of preconception exposure of PM2.5 on cardiac function in adult offspring. Methods and Results: Male and female friend leukemia virus b (FVB) mice were exposed to either filtered air (FA) or PM2.5 at an average concentration of 38.58 μg/m 3 for 6 hours/day, 5 days/week for 3 months. Mice were then crossbred into 2 groups: (1) FAmale ×FAfemale (both parents were exposed to FA preconception) and, (2) PM2.5male ×PM2.5female (both parents were exposed to PM2.5 preconception). Male offspring were divided: (1) preconception FA (offspring born to FA exposed parents) and, (2) preconception PM2.5 (offspring born to PM2.5 exposed parents) and analyzed at 3 months of age. Echocardiography identified increased left ventricular end systolic volume and reduced posterior wall thickness, reduced %fractional shortening and %ejection fraction in preconception PM2.5 offspring. Cardiomyocytes isolated from preconception PM2.5 offspring showed reduced %peak shortening, −dL/dT, TPS90 and slower calcium reuptake (tau). Gene and protein expression revealed modifications in markers of inflammation (IL‐6, IL‐15, TNFα, NFқB, CRP, CD26E, CD26P, intercellular adhesion molecule 1, and monocyte chemoattractant protein‐1) profibrosis (collagen type III alpha 1 chain), oxidative stress (NOS2), antioxidants (Nrf2, SOD, catalase), Ca 2+ regulatory proteins (SERCA2a, p‐PLN, NCX), and epigenetic regulators (Dnmt1, Dnmt3a, Dnmt3b, Sirt1, and Sirt2) in preconception PM2.5 offspring. Conclusions: Preconception exposure to PM2.5 results in global cardiac dysfunction in adult offspring, suggesting that abnormalities during development are not limited to the prenatal or postnatal periods but can also be determined before conception. Abstract : See Editorial by Stapleton